2016
DOI: 10.1017/dmp.2016.170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Real-Time Mortality Surveillance Based on Media Reports

Abstract: Objective We evaluated the usefulness and accuracy of media-reported data for active disaster-related mortality surveillance. Methods From October 29 through November 5, 2012, epidemiologists from the Centers for Disease Control and Prevention (CDC) tracked online media reports for Hurricane Sandy–related deaths by use of a keyword search. To evaluate the media-reported data, vital statistics records of Sandy-related deaths were compared to corresponding media-reported deaths and assessed for percentage matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Systematically collecting timely occupational data on ill persons during a pandemic can provide information about disproportionately affected occupational groups and improve recommendations to protect workers, the community, and public health. 35 , 36 , 37 In the absence of occupational data collected systematically through case report forms, we have demonstrated that the identification of COVID‐19 related deaths among a specific group of workers using media reports and union records can yield useful information about these decedents.…”
Section: Discussionmentioning
confidence: 99%
“…Systematically collecting timely occupational data on ill persons during a pandemic can provide information about disproportionately affected occupational groups and improve recommendations to protect workers, the community, and public health. 35 , 36 , 37 In the absence of occupational data collected systematically through case report forms, we have demonstrated that the identification of COVID‐19 related deaths among a specific group of workers using media reports and union records can yield useful information about these decedents.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, media mortality reports can provide vital information during a disaster to support evidence-based public health messaging to aim to minimize mortality and injury in near-real time in a less resource-intense manner. 22 Winter storms are the most common weather incident involving power outages, and the frequency and intensity of winter storms are increasing. 13,14 After a disaster, such as a winter storm, households may be without emergency health services and access to other resources.…”
Section: Discussionmentioning
confidence: 99%
“…Media reports have been used during other disasters, such as hurricanes, to augment traditional mortality surveillance methods and can help identify deaths quickly, provide situational awareness, and inform traditional surveillance activities and responses. 3,4 We used media reports to quickly document mortality among first responders early in the COVID-19 pandemic, when other sources of data on industry and occupation for COVID-19 cases were not widely available. Among a subset of deaths verified by jurisdictions, the sensitivity of the media scan was 88%.…”
Section: Discussionmentioning
confidence: 99%
“…Media reports can be used during disasters to augment traditional mortality surveillance methods and may provide more timely information than traditional surveillance. 3,4 Workers in law enforcement, fire, and emergency medical services (EMS) agencies (ie, first responders) are visible figures in their communities and essential critical infrastructure workers who may have occupational exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19. To gather timely information early in the COVID-19 pandemic among this workforce, we used media scan techniques to monitor publicly available reports of COVID-19–related deaths among first responders and verified that information with US public health jurisdictions.…”
mentioning
confidence: 99%